2021
DOI: 10.1128/aem.03144-20
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular and Intracellular Lanthanide Accumulation in the Methylotrophic Beijerinckiaceae Bacterium RH AL1

Abstract: Recent work in Methylorubrum extorquens AM1 identified intracellular, cytoplasmic lanthanide storage in an organism that harnesses these metals for its metabolism. Here, we describe the extracellular and intracellular accumulation of lanthanides in Beijerinckiaceae bacterium RH AL1, a newly isolated and recently characterized methylotroph. Using ultrathin-section transmission electron microscopy (TEM), freeze-fracture TEM (FFTEM), and energy-dispersive X-ray spectroscopy, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 78 publications
9
43
0
Order By: Relevance
“…Typical ones in ΔlanM and lanM-OX are shown. Similar deposits have been also observed in M. extorquens strain AM1 lut gene mutants (Roszczenko-Jasińska et al, 2020) and Beijerinckiaceae bacterium RH AL1 (Wegner et al, 2021).…”
Section: Subcellular Localization Of Lanm and La Deposition In The Cellssupporting
confidence: 82%
See 3 more Smart Citations
“…Typical ones in ΔlanM and lanM-OX are shown. Similar deposits have been also observed in M. extorquens strain AM1 lut gene mutants (Roszczenko-Jasińska et al, 2020) and Beijerinckiaceae bacterium RH AL1 (Wegner et al, 2021).…”
Section: Subcellular Localization Of Lanm and La Deposition In The Cellssupporting
confidence: 82%
“…It has been suggested that the protein shuttles Ln to Ln 3+ -dependent enzymes (Cotruvo et al, 2018;Cook et al, 2019). LanM also responds to Ln 3+ in non-methylotrophy settings in a methylotrophic Beijerinckiaceae bacterium RH CH11 (Wegner et al, 2021). lanM is associated with other lut genes in strain AM1 and PA1 genomes, but it is associated with the genes of different functions in strain 22A (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, crystalline lanthanum (La 3+ ) phosphate deposits were observed in the cytoplasm of M. extorquens by electron microscopy coupled with energy-dispersive X-ray spectroscopy ( 16 ). Extracellular (associated with outer membrane vesicles) as well as periplasmic deposits have also been described for the methylotroph Beijerinckiaceae bacterium RH AL1 ( 19 ). The exact composition, assembly, and function of these inclusions remain unclear.…”
mentioning
confidence: 95%